Bridging Culture and Mathematics: An Interactive Digital Module with Batik Pattern for Teaching the Concept of Area - Ismail, Agung Deddiliawan; Adityo, Adityo; Ekowati, Dyah Worowirastri; Yayik, Erna; Putri, Alfiani Athma (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Based on the results of observations and literature studies, it is evident that many students struggle to understand the concept of area. Most of them only memorize formulas. Additionally, many students have limited knowledge of the local culture. This study aims to develop interactive digital media based on local culture, specifically in the form of batik patterns, utilizing local materials. The research method used is Research and Development (R&D), employing the ADDIE method, which consists of Analysis, Design, Development, Implementation, and Evaluation. The study’s results stated that, according to the validator or media expert, the percentage was 92.86%, categorized as very feasible. The expert provided a percentage of 85.71%, which falls into the very feasible range. The results of the dissemination indicated that the students’ responses also showed the media to be very appropriate, with a percentage of 89.64%. The teachers’ responses, meanwhile, showed a percentage of 93.75%, which fell within the very feasible category—results of the Wilcoxon Test analysis using the signed rank method. The test shows a p-value of 7.45 × 10^(-9)< 0.05. It can be concluded that there is a significant increase in pre-test and post-test scores. The median score increased from 65.5 (IQR = 9.25) in the pre-test to 77.0 (IQR = 9.75) in the post-test, indicating an overall improvement in student performance. Furthermore, the calculated effect size (r = 0.85) suggests a large practical impact, confirming that the use of the interactive digital module with batik motifs substantially enhanced students’ conceptual understanding of area.